Modified versus three-level technique of retroperitoneal laparoscopic adrenalectomy for all patients with adrenal lesions ≤ 6cm: a retrospective, case-controlled study - Hu, Minxiong; Wu, Yangbiao; Xu, Xiao; Cai, Wenchao; Lin, Jiangui; Cai, Wanghai; Pan, Honghong; Yang, Zesong; Ye, Liefu; Wu, Jinfeng (Frontiers in Endocrinology, 2024)
Objectives The modified three-level technique for retroperitoneal laparoscopic adrenalectomy (RLA) has proven beneficial in the treatment of adrenal lesions in patients with BMI≥25 Kg/m2. This paper aims to summarize our institution’s seven-year experience using this technique for all patients with Adrenal Lesions ≤ 6cm. Patients and methods Between January 2016 and December 2022. The patients underwent laparoscopic adrenal surgery were categorized into Zhang’s technique (ZT) (Three-level Technique) group and modified technique (MT) group. The fundamental characteristics and perioperative data were analyzed, with statistical significance set at p<0.05. Results In total, 731 patients were stratified into two groups: ZT (n=448) and MT (n=283). Statistically significant distinctions were not detected between the two groups regarding sex, BMI, tumor location, tumor size, tumor type, or American Society of Anesthesiologists (ASA) score (p>0.05). The MT group demonstrated superior outcomes compared to the ZT group in terms of operative time, estimated blood loss, drainage volume, diet recovery time, complication rates, and postoperative hospitalization duration (p<0.05). 17 (4.34%) in the ZT group required unplanned adrenalectomy, while there was none in MT group (P<0.05). Conclusion MT retroperitoneal laparoscopic adrenalectomy has demonstrated its benefits in the treatment of adrenal lesions across all patients with adrenal lesions ≤ 6cm, serving as a valuable point of reference for the surgical management of adrenal diseases. Patient summary We have made modifications to the classic retroperitoneal laparoscopic adrenalectomy and achieved superior surgical outcomes, resulting in a procedure known as modified retroperitoneal laparoscopic adrenalectomy. This technique is suitable for both obese individuals and the general population with adrenal lesions ≤ 6cm.